Namibia : Staff Report for the 2006 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2007)
This 2006 Article IV Consultation highlights that with generally prudent macroeconomic policies, Namibia has enjoyed robust growth, moderate inflation, and strong external surpluses. Growth is expected to increase to 4 1\2 percent in 2006, after 4u percent in 2005, owing in part to a recovery in diamond production. Rising oil prices and interest rates have not yet noticeably affected activity. Public debt is poised to rise again over the medium term in light of an expected decline in custom union (SACU) receipts and an increase in spending to address Namibia's development needs.